Tropical reef fishes of Malaysia & Singapore - Allen, Gerald R. (Periplus Editions, 1996)
Fishes are by far the most abundant group of vertebrates approxinmately 24000 species inhabit fresh and marine waters. They are also the oldest backboned animals, having evoled in ancient seas nearly 500 million years ago.